Selection of Rhizosphere Bacterial Isolates and Development of Antagonistic Bacterial-Based Formulation to Control Fusarium Wilt on Shallot - Yadi Suryadi; Dwiningsih Susilowati; I Made Samudra (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2020)
Wilt disease caused by Fusarium spp. is a major disease in shallot-producing areas particularly in the North Coast of West Java. The research was aimed to select rhizosphere bacteria and develop an antagonistic bacterial-based formulation for its effectiveness to suppress wilt disease caused by Fusarium spp. on shallot plant under greenhouse and field trials. The field trials were carried out using randomized complete block design with four replications at the shallot farmer condition in Subang and Indramayu during the 2019 planting season. Antagonistic test of bacterial isolates from the rhizosphere showed that most of the bacterial isolates can be used as a biocontrol to Fusarium spp. pathogen. The result revealed that bacterial suspension formulation (E-76 + DBS-2 isolates) in combination with phytohormone (1:1 [v/v]) at Subang and Indramayu tended to suppress Fusarium wilt disease intensity with the disease inhibition ranging from 73.54–93.39% and 66.3–95.65%, respectively. The spraying application of formulation 2.5 ml/l was obtained as the best formula to suppress the disease. The growth and production of shallot were also affected by the application of antagonistic-bacterial formula.